Hukum Dan Pemberantasan Praktik Prostitusi : Kriminalisasi Pengguna Jasa Prostitusi Di Indonesia - Wardoyo, Rissa Asmitha; Agustanti, Rosalia Dika (Istinbath : Jurnal Hukum, 2021)
The practice of prostitution is a practice that is contrary to the principles of norms and ethics. It is often considered a practice that disrupts public order. This study aims to examine more deeply the development of prostitution in Indonesia and how to criminalize prostitution service users in Indonesia. This paper uses a normative legal research method, with a statutory approach, a conceptual approach, and a case approach. The results of the study show that increasingly sophisticated information and communication technology encourages the emergence of various new modus operandi in the practice of prostitution. Actors who previously had to do it face-to-face and meet in person at certain places when transacting can now do so by utilizing the features and various social media platforms available on smartphones. A large number of social media users encourages the increasing number of cases of prostitution in Indonesia. What's more, not everyone involved in this practice can be convicted, even if it's easy for users of prostitution services to escape the law, it's not a strange thing. This condition is caused by the absence of clear and firm regulations against prostitution service users, therefore, it is necessary to criminalize prostitution service users in the positive legal system in Indonesia to provide fear and deterrent effect for the perpetrators.